Enzymatic saccharification of liquid sugar from cassava peel starch: Optimization and characteristics - Maulidia, Indah; Rina, Oktaf; Shintawati; Elsyana, Vida; Ramandani, Adityas Agung; Siti Purnani, Mawar (Jurnal Rekayasa Proses, 2024)
The province of Lampung generated 2.6 million tons of cassava and 0.28 million tons of inner cassava peel waste in 2020. This demonstrates that the value of production is closely correlated with the amount of trash generated. 44-59% starch is still present in the waste from the inside of cassava peels, and this starch can be used as an input to make liquid sugar. Using the Response Surface Methodology (RSM) tool, this study attempts to optimize the saccharification process with modifications in duration (2, 4, and 8 h) and temperature (55, 60, and 65°C). Liquification and saccharification are the enzymatic processes used to make liquid sugar from cassava peel. According to study findings, the starch yield from cassava peels was 11.54%, with corresponding levels of water, ash, starch, and crude fiber of 13.53, 0.61, and 88.32%, and 1.025%, respectively. The yield of liquid sugar obtained from saccharification of cassava peel starch is 58.36%. The water and ash contents are 58.07, 16.95, and 0.11%, respectively, with the quality of lowering sugar content. Using the RSM approach, this study was able to optimize the saccharification process of liquid sugar from cassava peel starch at a temperature of 67.07 °C and a time variation of 6.8 hours. The optimized conditions resulted in a higher yield of liquid sugar from cassava peel starch. This study highlights the potential of utilizing cassava peels as a valuable source for liquid sugar production.